Manuscripts of the Latin Classics 800-1200 - Kwakkel, Erik (Leiden University Press, 2015)
This volume explores the production and use of medieval manuscripts that contain classical Latin texts. Six experts in the field address a range of topics related to these manuscripts, including how classical texts were disseminated throughout medieval society, how readers used and interacted with specific texts, and what these books look like from a material standpoint. This collection of essays also considers the value of studying classical manuscripts as a distinct group, and demonstrates how such a collective approach can add to our understanding of how classical works functioned in medieval society. Focusing on the period 800-1200, when classical works played a crucial role in the teaching of grammar, rhetoric, and dialectics, this volume investigates how classical Latin texts were copied, used, and circulated in both discrete and shared contexts.